(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical, paraclinical characteristics and evaluate the early treatment outcomes of hemopneumothorax in blunt chest trauma managed with minimally invasive pleural drainage. Subject and methods: A descriptive cross-sectional study was conducted on 30 patients with hemopneumothorax secondary to blunt chest trauma who were treated using minimally invasive pleural drainage at Nghe An 115 Surgical Hospital between October 2025 and January 2026. Results: The mean age of patients was 53,7 ± 15,1 years; males accounted for 83,3% of cases. The most common cause of injury was traffic accidents (46,7%). The most frequent clinical manifestations were chest pain (100%), dyspnea (83,3%), decreased breath sounds (100%), and chest wall abrasions (70%). On chest radiographs, rib fractures involving three or more ribs were most common (73,3%), predominantly affecting the posterior arches (73,3%). Computed tomography scans confirmed hemopneumothorax in 100% of patients. The mean duration of pleural drainage was 91,2 ± 18,4 hours, the mean initial drainage volume was 265 ± 249,5 ml. Favorable early treatment outcomes were achieved in 93,3% of patients, while the rate of adverse events and complications was 6,7%. Conclusion: Minimally invasive pleural drainage for the treatment of hemopneumothorax seondary to blunt chest trauma showed favorable early outcomes and a low complication rate in the studied patient group.